Anthem Maxx Tank Mixture Comparisons in Irrigated Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
The use of multiple herbicide modes of action in single versus sequential applications was examined for efficacy in corn. Common sunflower control was complete with all early postemergence and postemergence herbicides late in the season. Control of Russian thistle, Palmer amaranth, and green foxtail were 95% or more with all early postemergence and postemergence herbicides except Halex GT. All herbicide treatments increased grain yield 15–33% compared to the nontreated controls except Halex GT applied early postemergence.
Keywords: residual control; sequential application